[(η6‐Praziquantel)Cr(CO)3] Derivatives with Remarkable In Vitro Anti‐schistosomal Activity. Issue 7 (7th January 2013) - Patra, Malay; Ingram, Katrin; Pierroz, Vanessa; Ferrari, Stefano; Spingler, Bernhard; Gasser, Robin B.; Keiser, Jennifer; Gasser, Gilles
<x xml:space="preserve">Abstract</x> The antischistosomal effect of two [(η6‐praziquantel)Cr(CO)3] derivatives was investigated. The compounds (see figure: Cr purple, N blue, O red) were prepared in a one‐step procedure from commercially available praziquantel. Both derivatives show a high in vitro activity against Schistosoma mansoni, a parasitic trematode, and only a minor cytotoxic effect on selected mammalian cell lines.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>